The Viewpoint of Mothers on Pain Management in Neonatal Intensive Care Units - Mohammad Arshadi Bostanabad; Samaneh Alizadeh; Hossein Namdar Areshtanab; Soraya Nemati (Iran University of Medical Sciences, 2019)
Background: Parents play a vital role in the assessment and management of pain. There is limited knowledge about parental viewpoint or their participation in the pain management of the neonates admitted to the intensive care units. The present study aimed to assess the viewpoints of mothers about the pain management of neonates/ infants admitted to Tabriz hospitals. Methods: It was a descriptive cross-sectional study. A total of 255 mothers whose infants had been admitted to Neonatal Intensive Care Units (NICU) were recruited by convenience sampling method from September 2016 to August 2017. The required data were collected using a demographic questionnaire and PAIN questionnaire-Neonatal Intensive Care. The obtained data were analyzed using descriptive statistics in SPSS. Results: The Mean±SD age of the mothers was 28.38±6.10 years, and the majority of them (39%) had diploma. Among the mothers, 73% believed that their infants had experienced pain during admission to NICU. However, only 19% of the mothers stated that nurses tried to find the signs of pain in their infants; the majority of mothers (80%) indicated that to some extent, they were satisfied with the information they received from the treatment team regarding pain control for their newborns. Conclusion: Despite the prevalence of pain phenomenon in neonates, mothers' education for the symptoms of pain in their infants was inadequate. It seems that the mothers' participation in the pain management of their newborns makes them more capable of caring after discharge from the hospital. The study makes important findings available for future research.